Regional frequency analysis of heavy precipitation totals in the High Tatras region in Slovakia for flood risk estimation - GAÁL, Ladislav; SZOLGAY, Ján; LAPIN, Milan (Contributions to Geophysics and Geodesy, 2008)
Regional frequency analysis of heavy precipitation totals based on the estimation of parameters of the distribution function using L-moments has recently been adopted in the geographical-climatological conditions of Slovakia. On the basis of the most reliable records of daily precipitation totals from 56 climatological stations from the whole country, 3 homogeneous regions have been delineated for the purposes of the regional frequency analysis of 1 to 5-day precipitation maxima in warm/cold seasons, and the calendar year, respectively (Gaál, 2006). The recent study focuses on one of these regions consisting of 16 stations that also encompasses the whole High Tatras region. The paper as a case study presents a complete procedure of the estimation of the design precipitation along with the estimation of their uncertainty bounds.